Qualitative and quantitative research in Sociolinguistics: methodological dadaism? - Caroline Rodrigues Cardoso (Cadernos de Letras da UFF, 2013)
The confluence between quantitative and qualitative research in Sociolinguistics is a methodological Dadaism? The issue here is not epistemology, because I assume that the Sociolinguistics studies the language linked to social. I want to demonstrate that the methodological approach depends on the research question, ie, the subject about which a thesis is developed.